Flow cytometric analysis of pollen and spores: An overview of applications and methodology - Kron, Paul; Loureiro, João; Castro, Sílvia; Čertner, Martin (Cytometry. Part A, 2021)
Pollen grains are the male gametophytes in a seed-plant life cycle. Their small, particulate nature and crucial role in plant reproduction have made them an attractive object of study using flow cytometry (FCM), with a wide range of applications existing in the literature. While methodological considerations for many of these overlap with those for other tissue types (e.g., general considerations for the measurement of nuclear DNA content), the relative complexity of pollen compared to single cells presents some unique challenges. We consider these here in the context of both the identification and isolation of pollen and its subunits, and the types of research applications. While the discussion here mostly concerns pollen, the general principles described here can be extended to apply to spores in ferns, lycophytes, and bryophytes. In addition to recommendations provided in more general studies, some recurring and notable issues related specifically to pollen and spores are highlighted.
Keywords: Ploidies; buněčné jádro; Cell Nucleus; spory; Flow Cytometry; ploidie; průtoková cytometrie; Pollen; Spores; pyl